Mother's social status is associated with child health in a horticulturalist population. Issue 1922 (11th March 2020) - Alami, Sarah; von Rueden, Christopher; Seabright, Edmond; Kraft, Thomas S.; Blackwell, Aaron D.; Stieglitz, Jonathan; Kaplan, Hillard; Gurven, Michael
Abstract : High social status is often associated with greater mating opportunities and fertility for men, but do women also obtain fitness benefits of high status? Greater resource access and child survivorship may be principal pathways through which social status increases women's fitness. Here, we examine whether peer-rankings of women's social status (indicated by political influence, project leadership, and respect) positively covaries with child nutritional status and health in a community of Amazonian horticulturalists. We find that maternal political influence is associated with improved child health outcomes in models adjusting for maternal age, parental height and weight, level of schooling, household income, family size, and number of kin in the community. Children of politically influential women have higher weight-for-age ( B = 0.33; 95% CI = 0.12–0.54), height-for-age ( B = 0.32; 95% CI = 0.10–0.54), and weight-for-height ( B = 0.24; 95% CI = 0.04–0.44), and they are less likely to be diagnosed with common illnesses (OR = 0.48; 95% CI = 0.31–0.76). These results are consistent with women leveraging their social status to enhance reproductive success through improvements in child health. We discuss these results in light of parental investment theory and the implications for the evolution of female social status in humans.